Perancangan User Experience Aplikasi Merakit Komputer Pribadi - Dhani Muhammad Zidan; Agi Putra Kharisma; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The government issued a regulation on Pembatasan Pemberlakuan Kegiatan Masyarakat (PPKM). This regulation causes people to carry out their activities from home. In that case, a device such as a personal desktop is required. Computers that have been so usually have a higher price and do not necessarily suit the needs of consumers. Computer assembly is a great choice to get a computer that suits your needs and budget. In this case, not everyone understands the components needed and can assemble their own computer. With this problem in mind, the researcher designed a user experience application for assembling personal computers, later it was hoped that they could easily assemble their own computers. The method used by researcher is user centered design (UCD). Based on previous research using this method, the UCD method can produce innovative solutions that can solve a problem. The end result of this research is a high-fidelity prototype that has a good usability value and user experience value. Scores were obtained for three usability aspects, namely for the effectiveness aspect getting a score of 95%, for the efficiency aspect getting a score of 0.1387 goals/sec, for the satisfaction aspect using the system usability scale method and getting a score of 80% which is included in the perfect category. For better results, a user experience questionnaire test was carried out which gave above average results in the aspects of attractiveness and accuracy, then for the aspects of clarity, efficiency, stimulation, and novelty get a good results.